Assessment of High Frequency Imaging and Doppler System for the Measurements of the Radial Artery Flow-Mediated Dilation - NOWICKI, Andrzej; GAMBIN, Barbara; SECOMSKI, Wojciech; TRAWŃSKI, Zbigniew; SZUBIELSKI, Michał; TYMKIEWICZ, Ryszard; OLSZEWSKI, Robert (Archives of Acoustics, 2019)
Objectives: In the article we describe the new, high frequency, 20 MHz scanning/Doppler probe designed to measure the flow mediated dilation (FMD) and shear rate (SR) close to the radial artery wall.Methods: We compare two US scanning systems, standard vascular modality working below 12 MHz and high frequency 20 MHz system designed for FMD and SR measurements. Axial resolutions of both systems were compared by imaging of two closely spaced food plastic foils immersed in water and by measuring systolic/diastolic diameter changes in the radial artery. The sensitivities of Doppler modalities were also determined. The diagnostic potential of a high frequency system in measurements of FMD and SR was studied in vivo, in two groups of subjects, 12 healthy volunteers and 14 patients with stable coronary artery disease (CAD).Results: Over three times better axial resolution was demonstrated for a high frequency system. Also, the sensitivity of the external single transducer 20 MHz pulse Doppler proved to be over 20 dB better (in terms of a signal-to-noise ratio) than the pulse Doppler incorporated into the linear array. Statistically significant differences in FMD and FMD/SR values for healthy volunteers and CAD patients were confirmed, p-values < 0:05. The areas under Receiver Operating Characteristic (ROC) curves for FMD and FMD/SR for the prediction CAD had the values of 0.99 and 0.97, respectively.Conclusions: These results justify the usefulness of the designed high-frequency scanning system to determine the FMD and SR in the radial artery as predictors of coronary arterial disease.